Prevalence and associated factors of diabetes among adult populations of Hawassa town, southern Ethiopia: A community based cross-sectional study - Getu Kassa Belete; Hlupheka Lawrence Sithole (PLoS ONE, 2025)
Introduction Knowing the magnitude and preventable risk factors of diabetes has a significant contribution in targeted prevention intervention which ultimately ensures the existence of healthier and productive individuals in a country. Diabetes has untoward impact on health, social and economic consequences. Exploring preventable risk factors are extremely important because of their potential association and interaction with diabetes. Therefore, the aim of this study was to investigate the magnitude and modifiable risk factors of diabetes among adult populations in Hawassa town, southern Ethiopia. Methods A community based cross-sectional study was conducted from September, 2023 to November, 2023 among adult populations. A multi-stage sampling technique was employed to select 1,113 study participants between the ages of 20–69 years. An interviewer-administered questionnaire was used to collect data. Additionally, participants were also instructed to fast overnight, after which the standard fasting blood glucose test was conducted. A binary logistic regression model was fitted to identify independent predictors of diabetes. Results The overall prevalence of diabetes was 14.4% (95% Confidence Interval (CI): 12.4%, 16.4%). Being male (Adjusted Odds Ratio (AOR):2.10; 95% CI: 1.34, 3.29), being unable to read and write (AOR: 3.38; 95% CI: 1.09, 10.47), read and write (AOR: 3.38; 95% CI: 1.09, 10.47) and medium cycle (AOR 2.79; 95% CI: 1.02, 7.63) compared to college and above, consume less than 5 servings of fruits on daily base (AOR: 2.80; 95% CI: 1.18, 6.62), having ever chewed khat (AOR 6.50; 95% CI: 4.07, 10.39) and being overweight and obese (AOR: 2.43; 95% CI: 1.54, 3.83) were independently associated with diabetes mellitus (DM). Conclusion This study identified a high prevalence of diabetes among adults in Hawassa, driven by various risk factors. This presents an opportunity to mitigate diabetes risk through public health measures, including avoiding khat chewing, promoting healthy diets, managing overweight and obesity, implementing community-based screening, enhancing health literacy, and integrating health information into daily life.